Dermoscopy of discoid lupus erythematosus. - Idoudi, S.; Litaiem, N.; Ferjani, M.; Zeglaoui, F. (European Journal of Pediatric Dermatology, 2018)
Discoid lupus erythematosus (DLE) is a chronic inflammatory autoimmune cutaneous disease that can lead to significant disfiguration and scarring. Dermoscopy is a non-invasive tool whose applicability recently extended to the field of inflammatory skin disorders including DLE. We describe herein the use of dermoscopy to assess DLE activity in two female patients affected by LED from childhood.